Analysis of Utilization of Dried Leaves into Biobriquettes as Alternative Energy - Andre Ramadhan; Maharma Jelita (Universitas Negeri Padang, 2023)
The Faculty of Science and Technology, State Islamic University of Sultan Syarif Kasim Riau has a green open space with an area of about 1200mÂ² surrounded by trees. This green open space produces waste of dry leaves and twigs. Based on direct observation of the problems encountered, this dry leaf waste is handled by burning it directly by cleaning workers in the Faculty of Science and Technology. This study aims to determine the potential of dry leaf waste to become bio-briquettes and the potential of bio-briquettes to become electrical energy. In this study using the pyrolysis method using a pyrolysis furnace. The experimental results with a sample of 1 kg of dry leaves produced 14 pieces of biobriquettes weighing 100 grams, and producing a calorific value of 4493.40 cal/gram. If in a day 10 kg of dry leaves produce 140 pieces of biobriquettes weighing 100 grams, and produce a calorific value of 629,020 cal/gram. The potential for fuel power that can be generated is 3.0456 Watt. The potential for electrical energy from biobriquettes, assuming a PLTU efficiency of 25%, is 18.27 kWh per day, and in a month it can produce 548.1 kWh of electricity if the potential for waste is 300 kg collected in 1 month every day. The potential for electrical energy from the utilization of dry leaf waste can be used to supply electricity needs within the Faculty of Science and Technology UIN SUSKA Riau.